2004
DOI: 10.1080/14622200310001656939
|View full text |Cite
|
Sign up to set email alerts
|

Survey of subjective effects of smoking while drinking among college students

Abstract: Prevalence of tobacco use among the college-aged population is approximately 30%; a significant percentage of students initiate use or transition to regular use during their college years. This study examined the relationship between drinking and smoking rates, subjective reactivity of concurrent effects of alcohol and tobacco use, and expectations of smoking while under the influence of alcohol in first-year college students. The sample consisted of ever-smokers (n=217), who had smoked at least once in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
109
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(121 citation statements)
references
References 0 publications
10
109
0
1
Order By: Relevance
“…Daily smokers and nondaily smokers were more likely than nonsmokers to report exposure, which is not surprising given that they are more likely than other students to have friends who smoke and to frequent or live in locations where smoking occurs. Similarly, students who binge drink were more likely than other students to report exposure, which is likely to refl ect the co-occurrence of smoking and drinking among college students ( McKee, Hinson, Rounsaville, & Petrelli, 2004 ;Sher, Gotham, Erickson, & Wood, 1996 ). Living in residence locations associated with smoking, such as Greek houses and off-campus housing, also was associated with self-reported exposure.…”
Section: Discussionmentioning
confidence: 94%
“…Daily smokers and nondaily smokers were more likely than nonsmokers to report exposure, which is not surprising given that they are more likely than other students to have friends who smoke and to frequent or live in locations where smoking occurs. Similarly, students who binge drink were more likely than other students to report exposure, which is likely to refl ect the co-occurrence of smoking and drinking among college students ( McKee, Hinson, Rounsaville, & Petrelli, 2004 ;Sher, Gotham, Erickson, & Wood, 1996 ). Living in residence locations associated with smoking, such as Greek houses and off-campus housing, also was associated with self-reported exposure.…”
Section: Discussionmentioning
confidence: 94%
“…With our data, we cannot tell if the smoking was paired with the binge drinking. However, other research with emerging adults has found that drinking makes smoking more pleasurable ( McKee et al, 2004 ). Observational studies and real-time assessments should be conducted to examine these temporal associations.…”
Section: Discussionmentioning
confidence: 99%
“…A key stimulus for smoking is alcohol drinking ( Shiffman & Balabanis, 1996 ). McKee et al (2004) found that 74% of all smoking occasions among college students occurred while under the infl uence of alcohol, and this percentage was higher for light smokers (86%) than for heavier smokers (63%). Binge-drinking episodes increased the likelihood that smoking would occur and would be pleasurable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Light and intermittent smoking compared to heavy smoking are under more stimulus control and often occur under the influence of alcohol and in social situations [6,7]. Therefore, mechanisms of adolescent smoking cessation might differ from those of adults.…”
mentioning
confidence: 99%